2019
DOI: 10.3390/app9214569
|View full text |Cite
|
Sign up to set email alerts
|

Smart Parking: A Literature Review from the Technological Perspective

Abstract: The development and high growth of the Internet of Things (IoT) have improved quality of life and strengthened different areas in society. Many cities worldwide are looking forward to becoming smart. One of the most popular use cases in smart cities is the implementation of smart parking solutions, as they allow people to optimize time, reduce fuel consumption, and carbon dioxide emissions. Smart parking solutions have a defined architecture with particular components (sensors, communication protocols, and sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 114 publications
0
33
0
1
Order By: Relevance
“…Background: process mining in smart mobility and higher education Smart mobility Popular use case in the smart city domain is the implementation of smart parking solutions, which contributes to the optimisation of peoples' time, reduction of fuel consumption and carbon dioxide emissions (Barriga et al, 2019). The architecture of smart parking solutions is frequently characterised by three components -sensors, communication protocols, and software solutions (ibid).…”
Section: Methodsmentioning
confidence: 99%
“…Background: process mining in smart mobility and higher education Smart mobility Popular use case in the smart city domain is the implementation of smart parking solutions, which contributes to the optimisation of peoples' time, reduction of fuel consumption and carbon dioxide emissions (Barriga et al, 2019). The architecture of smart parking solutions is frequently characterised by three components -sensors, communication protocols, and software solutions (ibid).…”
Section: Methodsmentioning
confidence: 99%
“…A few recommendations, similar to those in [73], do not determine a particular type of sensor; however, the developers expect that a vehicle may contain cameras, ultrasonic sensors, and radar sensors. Different methodologies, such as that presented in [74], determine that the TSOP 1738 infrared sensor is accountable for identifying the presence or nonappearance of a vehicle. All things considered, the combination of sensors will surely deliver quality arrangement since the information will come from numerous sources that have various merits.…”
Section: Types Of Sensorsmentioning
confidence: 99%
“…Smart Parking solutions vary with regards to sensing technologies and methods that are used for parking space occupancy prediction and classification. When regarding the architecture of these solution it can be noticed that it is generally constituted out of three distinguishing components: type of sensors, network protocols, and software solutions [37]. In [38], the authors designed a prototype of a parking occupancy monitoring and visualization system that uses an ultrasonic sensor being controlled by an Arduino Uno which uses a Wireless XBee shield and an XBee Series 2 module for communication.…”
Section: State Of the Artmentioning
confidence: 99%
“…What is more, they are easy to implement (for instance, the Viterbi algorithm can be directly implemented as a computer algorithm) and they explicitly model the actual distribution of classes in classification problems, such as classifying a free parking space. With regards to radio technology, research of literature in [37] has shown that only 5% of researches up to date have employed LoRa for their Smart Parking Solution and, among these, none have used ML models for estimation or prediction. Although LoRa targets a wide range of applications, it has not yet been employed in a considerable amount in Smart Parking solutions [29].…”
Section: State Of the Artmentioning
confidence: 99%